Secure Cloud Storage with a Sanitizable Access Control System Again Malicious Data Publisher - Alfiya Khanum, R.M.; Chitra, K.; Noor Zuhaili, Md Yasin (INTI International University, 2024)
A novel encryption mechanism known as Ciphertext Policy of topic has been developed. Attribute Based Encryption (CPABE) was developed as an alternative to password-based systems to address the challenges associated with secure data sharing, where users are required to know the password for each file they need. This research work proposes a CPABE-based approach where just one secret key is required per user. A strategy has been implemented to establish precise document access control in a typical academic environment. Only users with the specified attribute similar to public key cryptography, can be encrypted many times to satisfy the access structure defined and allowing different users to decode the contents for secret retrieval. CP-ABE only necessitates a single encryption for each document due to its encoding. The idea of CPABE, which stands for Ciphertext-Policy Attribute-Based Encryption and analyses it in relation to other types of ABE, which stands for attribute-based encryption is developed here.